2017 IEEE 11th International Symposium on Diagnostics for Electrical Machines, Power Electronics and Drives (SDEMPED) 2017
DOI: 10.1109/demped.2017.8062363
|View full text |Cite
|
Sign up to set email alerts
|

Misalignment and unbalance fault severity estimation using stator current measurements

Abstract: Abstract-The feasibility of using stator current measurements in order to detect mechanical problems in electric rotating machinery has been proven by many authors several decades ago. However, this way of detecting problems has never been exploited as a full-covering and reliable prognostic monitoring technology. Although the imposed current-signatures of different evolving mechanical faults in electric machines are well characterized, the relation between the severity of those faults and the corresponding fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Verma and Kolekar applied a Fast Fourier Transform (FFT) to the stator current to detect shaft misalignment and showed [10]. Corne et al used spectral and wavelet analysis of stator currents to detect angular misalignment in permanent magnet synchronous motor drive systems and demonstrated which multiplicities of the failure frequency are the most sensitive to misalignment and the least sensitive to changes in motor operating conditions [31]. Goktas et al showed that a multilayer perceptron-based machine learning algorithm using vibration and stator current has an excellent performance in the automatic detection of parallel misalignment fault [32].…”
Section: Literatur Reviewmentioning
confidence: 99%
“…Verma and Kolekar applied a Fast Fourier Transform (FFT) to the stator current to detect shaft misalignment and showed [10]. Corne et al used spectral and wavelet analysis of stator currents to detect angular misalignment in permanent magnet synchronous motor drive systems and demonstrated which multiplicities of the failure frequency are the most sensitive to misalignment and the least sensitive to changes in motor operating conditions [31]. Goktas et al showed that a multilayer perceptron-based machine learning algorithm using vibration and stator current has an excellent performance in the automatic detection of parallel misalignment fault [32].…”
Section: Literatur Reviewmentioning
confidence: 99%
“…There are many approaches for condition monitoring of components through investigations of the motor current [26]. These range from wear detection of motors and bearings to characterisation [14,27] and system property change monitoring [28] he different system properties can result from geometrical differences in the components or different forms of wear [14,29]. Research results in condition monitoring by the motor current of ball screws drives (BSD) will be reviewed in depth.…”
Section: Current-based Component Wear Detectionmentioning
confidence: 99%
“…It must be noticed that detecting a 'small' misalignment does not imply that the machine is defective; whereas it is a sign of excessive loads that can easily lead to premature failure. Consequently, companies impose their own acceptable tolerance for judging the severity of misalignment [16].…”
Section: Misalignmentmentioning
confidence: 99%